2022
DOI: 10.1111/jfbc.14152
|View full text |Cite
|
Sign up to set email alerts
|

The health benefits of santol fruits and bioactive products isolated from Sandoricum koetjape Merr.: A scoping review

Abstract: The santol tree (Sandoricum koetjape Merr.) is largely distributed in Southeast Asia. It produces useful timber and edible fruits, consumed fresh, and transformed. It has a wide range of traditional medicinal uses for the treatment of inflammatory disorders and digestive troubles. Numerous bioactive natural products have been isolated from the roots, leaves, stems, and fruits of S. koetjape, including flavonoids, limonoids, and terpenoids. The seeds are considered toxic and contain insecticidal limonoids. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Triterpenoids from S. koetjape have ichthyotoxyc and anticarcinogenic effects (Ismail et al 2003). Koetjapic acid and tetracyclic triterpenoids from S. koetjape have antiangiogenic and antimetastatic effects (Bailly 2022). Triterpenoid compounds have various pharmacological activities.…”
Section: Discussionmentioning
confidence: 99%
“…Triterpenoids from S. koetjape have ichthyotoxyc and anticarcinogenic effects (Ismail et al 2003). Koetjapic acid and tetracyclic triterpenoids from S. koetjape have antiangiogenic and antimetastatic effects (Bailly 2022). Triterpenoid compounds have various pharmacological activities.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that KJA resulted in the inhibition of migration, differentiation, and altered expression of VEGF at the IC-50 of 18.4 μM, causing the suppression of angiogenesis. Moreover, KJA was also found to significantly inhibit the formation of micro-vessels in the aorta of rats with the same IC-50 value [ 12 , 19 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…is a medicinal plant belonging to the plant family Meliaceae, which is indigenous to Malaysia and the Southeast Asian region. It has a varied range of traditional medicinal applications for the curing of inflammatory conditions and digestive disorders ( 1 ).…”
Section: Introductionmentioning
confidence: 99%